Zestawienie jako narzędzie dowodzenia w sportowych komentarzach prasowych - Siekiera, Rafał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2016)
The article describes juxtaposition as a tool of argumentatio, used by sports journalists. As a powerful means of persuasion, juxtaposition can play different roles in a text. Sports journalists use juxtaposition to strengthen their arguments. As the research shows, it can form a part of various types of argument: ethical, pathetic (referring to the reader’s emotions), logical and referring to modality and value judgments. Juxtaposition can also be a part of the elocutio, thus improving the effectiveness of arguments. In some examples it also plays the role of the connector between the argumentatio and refutatio.